Battered African American women : a study of gender entrapment - Davis, Sharon Ellis (The Edwin Mellen Press, 2014)
A daring new model for ending Domestic Violence, this research seeks to engage black liberation theology and other movements intended to empower African American people who face racial injustice, and its impact on African American battered women.